2020
DOI: 10.15761/cogrm.1000305
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation services and COVID-19: the urgent need for phase two

Abstract: By the time of writing, epidemic in Italy, one of the countries at the epicentre of the European COVID-19 outbreak, has entered phase 2 with high levels of caution. The overall system has been burdened with the paralysis of standard practices dedicated to the delivery of health services. This interruption has included the provision of assisted reproductive treatments to infertile couples, apart from fertility preservation services to oncologic patients. On behalf of a tissue establishment inside a public hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Moreover, to diminish the exposure to the virus, treatment initiation was postponed for newly diagnosed patients, or a follow-up appointment was replaced with a telemedicine consultation. In Italy, a reduction of up to 65% in cancer patient addressability to FP procedures was mentioned, with a delay in new cancer diagnosis and reduced FP procedures [ 57 ]. Gupta et al demonstrated the effectiveness of fertility counseling for newly diagnosed cancer patients of reproductive age from 36.7% (June 2019–January 2020) to 70% (February 2021) [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, to diminish the exposure to the virus, treatment initiation was postponed for newly diagnosed patients, or a follow-up appointment was replaced with a telemedicine consultation. In Italy, a reduction of up to 65% in cancer patient addressability to FP procedures was mentioned, with a delay in new cancer diagnosis and reduced FP procedures [ 57 ]. Gupta et al demonstrated the effectiveness of fertility counseling for newly diagnosed cancer patients of reproductive age from 36.7% (June 2019–January 2020) to 70% (February 2021) [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…The experience on FP procedures of an Italian hospital-based tissue establishment during lockdown showed a reduction of 65% in cancer patient addressability, predominantly to the sperm bank. The authors speculate that COVID-19 induced general paralysis of the healthcare system and was associated with a delay in new cancer diagnosis, subsequently diminishing FP demand [ 57 ].…”
Section: What Are the Issues That Might Hamper A Safe Oncofertility P...mentioning
confidence: 99%
See 1 more Smart Citation